CHARACTERISTICS OF RENDZINA SOILS IN SERBIA AND THEIR WRB CLASSIFICATION - Radmanović, Svjetlana B. (Journal of Agricultural Sciences (Belgrade), 2020)
According to the soil classification system used in Serbia, Rendzina is a soil type with an A-AC-C-R profile, developed on parent rock containing more than 20% of calcareous material (except soils with an A-R profile on hard pure limestone or dolomite). Previous instigations have shown that 29 Rendzina soil profiles from Serbia belong to the reference soil groups (RSGs) of Leptosols, Regosols and Phaeozems according to the World Reference Base for Soil Resources (WRB 2015). The present study addresses the correlations among three WRB RSGs in terms of soil texture, mean weight diameter (MWD), total N content, and humus fractional composition using Principal Component Analysis (PCA). The objective is to better understand the mutual relationship between the classification soil units used in Serbia and the international WRB system. The results show that PCA cannot unequivocally distinguish between these three RSGs. Leptosols and Regosols are highly incoherent group while Phaeozems is highly coherent, leading to the conclusion that the physical and chemical properties of the soil profiles of Phaoeozems are specific. It is obvious that soil depth and color, which are the overriding factors in the differentiation of Rendzina soils into three WRB RSGs, had no significant effect on these properties. The results further show that soil properties such as texture, MWD, humus fractional composition, etc. cannot be used to correlate Rendzina soils from Serbia with WRB. Instead, careful correlation is needed of individual soil profiles based on quantitative soil data analysis as required by WRB.